Visual outcome of pressurised bottled drinks related eye injuries in Ibadan (2003)
Records of 15 patients presenting with pressurised bottled drinks related eye injuries between January 1996 and 2001 were reviewed to identify factors contributing to accidental eye injuries from pressurised bottled drinks, reason for poor outcome and to make recommendations. In all, 16 eyes of 15 patients were studied out of which 7 were males (M:F, ratio I :1.1). Age range, 3 years-49 years, mean 23.6 years. The majority of those affected were students 46.7%, and traders 26.7%. The commonest activity leading to injury was explosion during the process of arranging the bottles or crates of drinks (43.8%) and accidental fall of bottle from hand or height (37.5%). Drinks implicated include, Coca-cola 50%, beer 25%, others (Fanta, Legend stout, Mirinda, Grape juice) 25%. Complications arising from the injury included, hyphema 43.8%, vitreous haemorrhage 12.5%, and retinal detachment 12.5%. The globes were retained in 12 (75%) cases, 3 defaulted and one eye became phthisical. The final visual acuity was 6/18 or better in 25%, between 6/24 and 6/60 in 12.5% and less than 6/60 in 31.3 %. The final visual acuities of three patients who were lost to follow up were unknown. Reason for poor visual outcome include severity of injury with resultant serious complications, and delay with instituting surgical treatment. Eye injuries resulting from exploding bottled drinks are potentially very serious and therefore best prevented. It is recommended that conversion of bottled drinks to canned or plastic containers be considered by the manufacturers. Greater care should be taken with the handling of bottled drinks by the sellers, factory workers and consumers. High risk occupations such as bottled drink sellers and factory workers may need to wear protective goggles during handling. Public health education on need to seek prompt and proper treatment as well as need for Government to institute the National health insurance scheme to cater for indigent patients.